2020
DOI: 10.1016/j.heliyon.2020.e03913
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors of inpatient hypoglycemia: A systematic review

Abstract: Hypoglycemia is an important and harmful complication of Diabetes Mellitus (DM) that often occurs in inpatient or outpatient settings. Hypoglycemia can be divided into two types, i.e. primary hypoglycemia when hypoglycemia is the main diagnosis for admission, whereas secondary hypoglycemia if hypoglycemia occurs during hospitalization. Hypoglycemia during hospitalization or secondary hypoglycemia may arise from various risk factors, such as advanced age, comorbid diseases, type of diabetes, previous history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 32 publications
2
27
2
6
Order By: Relevance
“…On admission (the first occasion if there were subsequent hospitalizations) they were of mean±SD age 73.1±12.5 (range 44.1-96.7) years, 34 (57.6%) were males, and 51 (86.4%) had type 2 diabetes. Diabetes duration, available for 35 patients, was a median [inter-quartile range (IQR)] 20 [15][16][17][18][19][20][21][22][23][24][25][26][27][28] years. The majority of the 59 patients (78.9%) were insulin-treated, and 12.5% were taking a sulfonylurea with one of these also using insulin.…”
Section: Resultsmentioning
confidence: 99%
“…On admission (the first occasion if there were subsequent hospitalizations) they were of mean±SD age 73.1±12.5 (range 44.1-96.7) years, 34 (57.6%) were males, and 51 (86.4%) had type 2 diabetes. Diabetes duration, available for 35 patients, was a median [inter-quartile range (IQR)] 20 [15][16][17][18][19][20][21][22][23][24][25][26][27][28] years. The majority of the 59 patients (78.9%) were insulin-treated, and 12.5% were taking a sulfonylurea with one of these also using insulin.…”
Section: Resultsmentioning
confidence: 99%
“…Hypoglycemia frequently occurs in diabetic patients undergoing pharmacotherapy and is difficult to predict[ 1 - 4 ]. In the present study, we have demonstrated that FBH also occurs in non-diabetic people, although the prevalence was very low (less than 1.0% of the total) in the general population studied, in contrast to that in diabetic patients[ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fasting plasma glucose was measured (approximately 54% of samples) mainly by spectrophotometric or potentiometric (approximately 30%) method[ 8 ]. FBH was defined as an FPG < 70 mg/dL (3.9 mmol/L), regardless of the presence or absence of symptoms[ 4 , 10 ]. Laboratory measurements were performed using standard automated methods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations